PENGARUH STRUKTUR MODAL TERHADAP PROFITABILITAS SERTA DAMPAKNYA PADA NILAI PERUSAHAAN - Laura Victoria (Program Studi Ilmu Administrasi Bisnis, UPN Veteran Yogyakarta, 2019)
The objective of this research is to know the influence of the capital structure ( Debt to Equity Ratio /DER and the Debt to Asset Ratio/DAR) on Profitability (Return on Equity/ROE) and its impact on firm value (Price to Book Value/PBV). Sample used 21 banking whose listed at 2012-2016 on the Indonesian stock exchange. The research types was explanatory, where data obtained from official website of the Indonesian stock exchange. The sampling technique used purposive sampling. Path analysis used for analyzed the influence between variables. T-test and sobel test used for test the hypothesis. Based on the result, there were no significantly influence of the capital structure (DER and DAR) on firm value (PBV), but the capital structure (DER) has significantly effect on the profitability (ROE). Furthermore, the profitability (ROE) has significantly effect on firm value (PBV) and also able to mediate the influence of the capital structure (DER) on firm value (PBV). The banking sector must maintain ROE levels because it has an significantly effect on PBV, and important for maintain firm value. Keywords: capital structure, profitability, firm value.